2015
DOI: 10.5152/tjg.2014.4768
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose ramosetron accelerates gastric emptying in the early phase: A crossover study in healthy volunteers using a continuous real-time 13C breath test (BreathID System)

Abstract: Background/Aims: The aim of this study was to determine the correlation between low-dose ramosetron pretreatment and gastric emptying using a novel, non-invasive technique for measuring gastric emptying, namely, the continuous real-time 13C breath test (BreathID system: Exalenz Bioscience Ltd., Israel). Materials and Methods: Twelve healthy male volunteers participated in this randomized two-way crossover study. The subjects fasted overnight and were randomly assigned to receive the test meal (200 kcal per 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Further studies will be warranted to determine whether the early phase of gastric emptying such as AUC 5 value was associated with pancreatic enzyme abnormalities in FD patients. In addition, previous studies have reported that solid test meals [43] and liquid meals [44][45][46] were used for assessment of the early phase of gastric emptying. In the future, we have to compare the early phase of gastric emptying evaluated by solid test meals with liquid test meals.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be warranted to determine whether the early phase of gastric emptying such as AUC 5 value was associated with pancreatic enzyme abnormalities in FD patients. In addition, previous studies have reported that solid test meals [43] and liquid meals [44][45][46] were used for assessment of the early phase of gastric emptying. In the future, we have to compare the early phase of gastric emptying evaluated by solid test meals with liquid test meals.…”
Section: Discussionmentioning
confidence: 99%